Synthesis and characterization of Sr2Be2B2O7 by XRD and FTIR - (:unkn) unknown (BULGARIAN ACAD SCIENCE, 2017)
In this work pure Sr2Be2B2O7 material was prepared by solid- state reaction at 950 degrees C in air. The stoichiometric amounts of SrO, BeO and H3BO3 were used as starting materials. Phase analysis of the synthesized materials was carried out using powder X-ray diffraction (XRD). They were characterized by Fourier transform infrared spectroscopy (FTIR) as well.
Keywords: strontium beryllium borate; XRD; FTIR; PHOTOLUMINESCENCE; CRYSTAL